HBR's 10 must reads 2015 the definitive management ideas of the year from Harvard business review. - Harvard Business Review (Boston Harvard Business Review Press, 2015)
We?ve combed through ideas, insights, and best practices from the past year of Harvard Business Review to help you get up to speed fast on the freshest, most relevant thinking driving business today. With authors from Clayton Christensen to Roger Martin and company examples from Netflix to Unilever, this volume brings the most current and important management conversations to your fingertips.
Keywords: Management